If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 3) = 5(x + -4) Reorder the terms: 2(3 + 3x) = 5(x + -4) (3 * 2 + 3x * 2) = 5(x + -4) (6 + 6x) = 5(x + -4) Reorder the terms: 6 + 6x = 5(-4 + x) 6 + 6x = (-4 * 5 + x * 5) 6 + 6x = (-20 + 5x) Solving 6 + 6x = -20 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6 + 6x + -5x = -20 + 5x + -5x Combine like terms: 6x + -5x = 1x 6 + 1x = -20 + 5x + -5x Combine like terms: 5x + -5x = 0 6 + 1x = -20 + 0 6 + 1x = -20 Add '-6' to each side of the equation. 6 + -6 + 1x = -20 + -6 Combine like terms: 6 + -6 = 0 0 + 1x = -20 + -6 1x = -20 + -6 Combine like terms: -20 + -6 = -26 1x = -26 Divide each side by '1'. x = -26 Simplifying x = -26
| -3(x+5)=2-2x | | 12x^2+4x+15=0 | | 3(7r-12)=21r-6 | | 63+30t+3t^2=0 | | 4x+2.9=9.7 | | 7(x+1)=-2(x-4)+x | | 12k-3(2k-3)=45 | | -5y-15=7y+9 | | -5-15=7y+9 | | 2(1.6x)-1.33=-x+4.13 | | 4z+17=3z+4 | | 5-2x-4x=9 | | 27(2/3n) | | 500/3000 | | 7/3xb^4 | | y=-15-(-2)-(11-6) | | 2x^2y+4xy-58y=0 | | y=-20+30-40-(-50) | | (10-y)+y=3.09 | | y=x^3+2x^2-8x-5 | | (9+z)(5z+3)=0 | | 5x^3+40x^2+60x=0 | | Z=23 | | 2x-8+2=x-3+5 | | f(x)=x^3+2x^2-8x-5 | | 4x(2x-1)^1/2 | | n^2-19n+10=0 | | 7(3-z)6=-z | | 1/3x+2=1/6x+4/3 | | 3y=2x+b | | 3(x+7)-2x=3+2x | | Y=x^4-3x^2 |